Association between eprosartan-based hypertension therapy and improvement in cognitive function score: long-term follow-up from the OSCAR observational study. (June 2015) - Hanon, Olivier; Lee, Yong-Seok; Pathak, Atul; ,
Objective: The Observational Study on Cognitive function And systolic blood pressure Reduction (OSCAR) was designed to evaluate the impact of eprosartan-based therapy on cognitive function in a cohort of 25, 745 hypertensive subjects followed for six months. Methods: In this supplementary analysis, we studied the relationship between eprosartan-based therapy and cognitive function (assessed using the Mini-Mental State Examination (MMSE)) after 12-month follow-up of 3600 patients (the long-term follow-up on-treatment population). Results: Reduction in blood pressure was sustained over 12 months, with mean systolic blood pressure/diastolic blood pressure 130.9/79 mmHg at one year, compared with 164.3/92.8 mmHg at baseline ( p <0.001). The overall mean MMSE score at completion of 12-month follow-up was significantly increased from baseline (27.8±2.7 vs. 26.3±3.5; p <0.001). The increase in MMSE score was observed when the population was stratified by age ( p <0.001) and in a subgroup of patients with cerebrovascular disease at baseline ( n =290) ( p <0.001, 12 months vs . baseline). Conclusions: In this cohort of patients, use of eprosartan-based treatment for one year was associated with sustained reduction in blood pressure and stabilization or improvement of MMSE scores. These data are supportive of a role for blood pressure control in the prevention or delay of cognitive decline.